Dlaczego pojawiła się miłość? Ewolucja monogamicznego systemu kojarzenia u ludzi - Budzicz, Łukasz (My University, 2011)
The article presents basic information about the evolution of mating system, which occurs in humans. In nature, the three major evolutionary pressures promote the long-term monogamous relationships: significantly enhanced offspring survival when both parents provide care, certainty of paternity and limited opportunities to find a new mate. All these factors are present in humans and may also to some extent explain the present diversity of human reproductive behaviors. A hypothetical model of the evolution of human reproductive behavior proposed by David Geary is also discussed.
Why is there love? The EVO LUTION of monogamous mating system in humans